THE PROBLEMATICS OF EXECUTION LAW AGAINST NON-EXECUTABLE JUDGMENTS AND COMPARISONS WITH MALAYSIAN LAW - Ariadi Subagyono, Bambang Sugeng; Anand, Ghansham (Fakultas Syariah, 2018)
In public courts, the litigation of civil case is under civil law procedure. This is a legal regulation to maintain material civil laws. The procedural law is also a way to file a particular civil case to civil court and to organize judgesâ€™ ways in making judgment toward legal subject. Civil law procedure prevents any vigilante actions that creates public legal order. Judiciaries provide protection for legal subject in preserving their rights and prevent any arbitrary actions. After case investigation process set under procedural law, a court judgment is made to judge and solve case. Legal actions are subsequently conducted to reach fixed legal judgment (inkracht van gewijsde). Some executions for civil cases in Indonesia is suspended since the object is different from reality or non-executable. Furthermore, civil case judgment is sometimes contradictory to criminal cases, although the objects are similar. Either litigant and/or defendant files request to the Supreme Court to have a legal protection or the chairman of district court requests for an instruction from the Supreme Court, may suspend court judgment. Therefore, the implementation of court judgments with legal power is still undeniably problematic. If the execution is suspended or not allowed, it may disadvantage â€œthe justice seekersâ€; public society. The suspended or non-executable judgment should be immediately addressed on its implementation, instead of its law.Di pengadilan umum, proses kasus perdata berada dalam prosedur hukum perdata. Ini adalah peraturan hukum untuk mempertahankan hukum sipil material. Undang-Undang prosedural ialah cara mengajukan kasus perdata ke pengadilan sipil dan mengatur cara hakim memutuskan subjek hukum. Prosedur hukum perdata bertujuan mencegah tindakan hakim-sendiri sehingga tercipta tatanan hukum publik. Peradilan memberikan perlindungan bagi subjek hukum dalam melestarikan haknya dan mencegah kesewenang-wenangan. Setelah proses penyelidikan kasus sebagaimana diatur dalam hukum prosedural, putusan pengadilan dibuat untuk menilai dan memecahkan kasus. Tindakan hukum selanjutnya dilakukan hingga mendapat keputusan hukum tetap (inkracht van gewijsde). Beberapa putusan kasus perdata Indonesia ditangguhkan karena objek berbeda dari kenyataan atau tidak dapat dieksekusi. Selanjutnya, putusan kasus perdata terkadang bertentangan dengan kasus pidana, meskipun objeknya sama. Baik penggugat dan/atau terdakwa mengajukan permintaan ke Mahkamah Agung untuk memiliki perlindungan hukum atau ketua dari pengadilan distrik meminta instruksi dari Mahkamah Agung, bisa menangguhkan keputusan pengadilan. Karenanya, pelaksanaan putusan pengadilan dengan kekuatan hukum masih bermasalah. Jika eksekusi ditangguhkan atau tidak diizinkan, tentu dapat merugikan â€œpara pencari keadilanâ€; masyarakat umum. Putusan yang ditangguhkan atau tidak dapat dieksekusi harus segera ditangani pada pelaksanaannya, bukan hukumnya.